Lithium: Potential Therapeutics Against Acute Brain Injuries and Chronic Neurodegenerative Diseases - Akihiko Wada; Hiroki Yokoo; Toshihiko Yanagita; Hideyuki Kobayashi (Elsevier, 2005)
In addition to the well-documented mood-stabilizing effects of lithium in manic-depressive illness patients, recent in vitro and in vivo studies in rodents and humans have increasingly implicated that lithium can be used in the treatment of acute brain injuries (e.g., ischemia) and chronic neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, tauopathies, and Huntington's disease). Consistent with this novel view, substantial evidences suggest that depressive illness is not a mere neurochemical disease, but is linked to gray matter atrophy due to the reduced number/size of neurons and glia in brain. Importantly, neurogenesis, that is, birth/maturation of functional new neurons, continues to occur throughout the lifetime in human adult brains (e.g., hippocampus); the neurogenesis is impaired by multiple not-fully defined factors (e.g., aging, chronic stress-induced increase of glucocorticoids, and excitotoxicity), accounting for brain atrophy in patients with depressive illness and neurodegenerative diseases. Chronic treatment of lithium, in agreement with the delayed-onset of mood-stabilizing effects of lithium, up-regulates cell survival molecules (e.g., Bcl-2, cyclic AMP-responsive element binding protein, brain-derived neurotrophic factor, Grp78, Hsp70, and β-catenin), while down-regulating pro-apoptotic activities (e.g., excitotoxicity, p53, Bax, caspase, cytochrome c release, β-amyloid peptide production, and tau hyperphosphorylation), thus preventing or even reversing neuronal cell death and neurogenesis retardation. Keywords:: lithium neuroprotection/neurogenesis, glycogen synthase kinase-3, brain-derived neurotrophic factor, Bcl-2, cyclic AMP-responsive element binding protein